Antioxidant Enzyme Activities Estimation In vicia faba Leaves - Al-Yassiry, Zahraa A.N. (International Journal of Scientific Research in Biological Sciences, 2024)
Plant cells have the inherent ability to produce reactive oxygen species and oxygen radicals as secondary products during various physiological processes associated with abiotic stress. The disruption of the equilibrium between the generation of reactive oxygen species and the defense systems against oxidative harm is a significant consequence of abiotic stress in plants. As a consequence, the accumulation of reactive oxygen species occurs, hence triggering the onset of oxidative stress. Jasmonates represent a class of plant hormones that exert significant regulatory influence over several physiological processes. These processes include gene and metabolic regulation, immune mechanisms, responses to stress, reproductive activities, and interaction between cells, among other roles. The presence of oxidative stress induces the synthesis of metabolites possessing antioxidant characteristics and augments the efficacy of antioxidant enzymes, hence conferring a safeguarding impact on plant tissues. The aim of this study was to investigate the effects of methyl jasmonate (JAME) administration on reactive oxygen species and the activities of H2O2 scavenging enzymes, namely superoxide dismutase, catalase and glutathione in vicia faba leaves. After implementing a therapy strategy with JAME, there was an elevation in the activity levels of the enzyme superoxide dismutase , catalase , and glutathione.